Avifauna in Logged-Over Forest of Upper Baleh, Sarawak - Tuen, Andrew Alek; Sapian, Attiqqah Fadziliah; Ismail, Khatijah; Peter, Cindy; Haba, Mohd Hasri Al-Hafiz; Lee, Ch'ien C (Borneo Journal of Resource Science and Technology, 2018)
Commercial logging is a major economic activity in the Upper Baleh catchment, Sarawak, so logged-over forest is the dominant forest type there. Avifauna survey was conducted in the logged-over forest of Upper Baleh in November 2015 as part of the Upper Baleh Heart of Borneo Expedition. The objective of the survey was to collect baseline data on the avifauna species that inhabit the study area, their conservation status and feeding guilds. Both mist-net and observation method were used. A total of 95 species of birds was recorded: 36 species via mist-nets and 69 species via observation. Little spiderhunter was the dominant species, accounting for 33% of mist-netted bird. Seven species are Totally Protected including six species of hornbills and a Great Argus Pheasant, while 18 other species are Protected under the Sarawak Wild Life Ordinance 1998. The majority of the birds are insectivorous (55.8%), foraging either at ground level (babblers), along the tree trunks or branches (woodpeckers) or at the canopy (flycatchers). Omnivorous birds, which feed on two or more types of diet, accounted for 48.4% of the avifauna species recorded and these include bulbuls and hornbills. The diverse community of bird, including the protected species, makes the area an attractive birding destination for visitors since now part of the catchment has been gazetted as a national park. Avifauna’s role as pollinating and dispersing agent will help the logged-over forest to recover. Keywords: conservation status, feeding guilds, Heart of Borneo, logging roads